Jinhua Qinggan granules attenuates acute lung injury by promotion of neutrophil apoptosis and inhibition of TLR4/MyD88/NF-κB pathway. (30th January 2023) - Zhu, Yanhui; Han, Qianqian; Wang, Lei; Wang, Baiyan; Chen, Jianshuang; Cai, Bangrong; Wu, Can; Zhu, Xiali; Liu, Fugang; Han, Deen; Dong, Haoran; Jia, Yongyan; et al.
Abstract: Ethnopharmacological relevance: Acute lung injury (ALI) is one of the fatal complications of respiratory virus infections such as influenza virus and coronavirus, which has high clinical morbidity and mortality. Jinhua Qinggan granules (JHQG) has been approved by China Food and Drug Administration in the treatment of H1N1 influenza and mild or moderate novel coronavirus disease 2019 (COVID-19), which is an herbal formula developed based on Maxingshigan decoction and Yinqiao powder that have been used to respiratory diseases in China for thousands of years. However, the underlying mechanism of JHQG in treating infectious diseases remains unclear. Aim of the study: This study investigated the effects of JHQG on neutrophil apoptosis and key signaling pathways in lipopolysaccharide (LPS) -induced ALI mice in order to explore its mechanism of anti-inflammation. Materials and methods: The effect of JHQG on survival rate was observed in septic mouse model by intraperitoneal injection of LPS (20 mg/kg). To better pharmacological evaluation, the mice received an intratracheal injection of 5 mg/kg LPS. Lung histopathological changes, wet-to-dry ratio of the lungs, and MPO activity in the lungs and total protein concentration, total cells number, TNF-α, IL-1β, IL-6, and MIP-2 levels in BALF were assessed. Neutrophil apoptosis rate was detected by Ly6G-APC/Annexin V-FITC staining. Key proteins associated with apoptosis including caspase 3/7 activity, Bcl-xL and Mcl-1 were measured by flow cytometry and confocal microscope, respectively. TLR4 receptor and its downstream signaling were analyzed by Western blot assay and immunofluorescence, respectively. Results: JHQG treatment at either 6 or 12 g/kg/day resulted in 20% increase of survival in 20 mg/kg LPS-induced mice. In the model of 5 mg/kg LPS-induced mice, JHQG obviously decreased the total protein concentration in BALF, wet-to-dry ratio of the lungs, and lung histological damage. It also attenuated the MPO activity and the proportion of Ly6G staining positive neutrophils in the lungs, as well as the MIP-2 levels in BALF were reduced. JHQG inhibited the expression of Mcl-1 and Bcl-xL and enhanced caspase-3/7 activity, indicating that JHQG partially acted in promoting neutrophil apoptosis via intrinsic mitochondrial apoptotic pathway. The levels of TNF-α, IL-1β, and IL-6 were significantly declined in LPS-induced mice treated with JHQG. Furthermore, JHQG reduced the protein expression of TLR4, MyD88, p-p65 and the proportion of nuclei p65, suggesting that JHQG treatment inhibited TLR4/MyD88/NF-κB pathway. Conclusion: JHQG reduced pulmonary inflammation and protected mice from LPS-induced ALI by promoting neutrophil apoptosis and inhibition of TLR4/MyD88/NF-κB pathway, suggesting that JHQG may be a promising drug for treatment of ALI. Graphical abstract: Image 1 Highlights: Jinhua Qinggan granules promotes neutrophil apoptosis via intrinsic apoptotic pathway. Jinhua Qinggan granules inhibits TLR4/MyD88/NF-κB signaling pathway. Jinhua Qinggan granules alleviates lipopolysaccharide-induced pulmonary inflammation.